Measurement properties for muscle strength tests following anterior cruciate ligament and/or meniscus injury: What tests to use and where do we need to go? A systematic review with meta-analyses for the OPTIKNEE consensus. Issue 24 (16th September 2022) - Urhausen, Anouk P; Berg, Bjørnar; Øiestad, Britt Elin; Whittaker, Jackie L; Culvenor, Adam G; Crossley, Kay M; Juhl, Carsten B; Risberg, May Arna
Abstract : Objectives: Critically appraise and summarise the measurement properties of knee muscle strength tests after anterior cruciate ligament (ACL) and/or meniscus injury using the COnsensus-based Standards for the selection of health Measurement INstruments Risk of Bias checklist. Design: Systematic review with meta-analyses. The modified Grading of Recommendations Assessment, Development and Evaluation-guided assessment of evidence quality. Data sources: Medline, Embase, CINAHL and SPORTSDiscus searched from inception to 5 May 2022. Eligibility criteria for selecting studies: Studies evaluating knee extensor or flexor strength test reliability, measurement error, validity, responsiveness or interpretability in individuals with ACL and/or meniscus injuries with a mean injury age of ≤30 years. Results: Thirty-six studies were included involving 31 different muscle strength tests (mode and equipment) in individuals following an ACL injury and/or an isolated meniscus injury. Strength tests were assessed for reliability (n=8), measurement error (n=7), construct validity (n=27) and criterion validity (n=7). Isokinetic concentric extensor and flexor strength tests were the best rated with sufficient intrarater reliability (very low evidence quality) and construct validity (moderate evidence quality). Isotonic extensor and flexor strength tests showed sufficient criterion validity, while isometric extensor strength tests had insufficient construct and criterion validity (high evidence quality). Conclusion: Knee extensor and flexor strength tests of individuals with ACL and/or meniscus injury lack evidence supporting their measurement properties. There is an urgent need for high-quality studies on these measurement properties. Until then, isokinetic concentric strength tests are most recommended, with isotonic strength tests a good alternative.